If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5x + -9) = 102 Reorder the terms: -3(-9 + 5x) = 102 (-9 * -3 + 5x * -3) = 102 (27 + -15x) = 102 Solving 27 + -15x = 102 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -15x = 102 + -27 Combine like terms: 27 + -27 = 0 0 + -15x = 102 + -27 -15x = 102 + -27 Combine like terms: 102 + -27 = 75 -15x = 75 Divide each side by '-15'. x = -5 Simplifying x = -5
| 12-z=11 | | -4(-3+6x)=108 | | 13-y=1 | | 2(7+q)=14+2q | | 7/84=12/× | | 5w-4w=15 | | 7_84=12/× | | 4(6x+4)=64 | | 14-x=2 | | 17x+3y=15 | | 2p-p=7 | | 5(-6x+2)=10 | | -7(5x+2)=-364 | | 10u-9u=10 | | 2+9x=-43 | | 7(7+5x)=-56 | | 8.25t+9=14.5t+14 | | 4(-10-x)=4 | | -13b+18-15=2b+17-14b | | 29=10x-51 | | 8y-10y=3y+25 | | 5+3(3x-5)=7-4(2x+1) | | 2/9=1/3-4/9 | | 8-1/3n-13 | | 4(-3x-3)=-156 | | x+1200p=700 | | -7(x-4)+x=-2-x | | -4(3+3x)=-12 | | 2/9=1/3-4/9n | | 2x-4=13x+51 | | 5x-6y=x+4y | | -3(1+5x)=177 |